THE RELATIONSHIP BETWEEN MATERNAL HEIGHT DURINGPREGNANCY AND THE INCIDENCE OF STUNTING IN TODDLERS AT THERONGKOP COMMUNITY HEALTH CENTER, GUNUNG KIDUL IN 2025 - Eka Oktavia; Lara Audi Setyawati (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Stunting is a global nutrition problem. World Health Organization Data shows that as many as 22% of toddlers experience stunting, which can affect children's cognitive development in the future. The incidence of stunting in Indonesia remains high in 2024 according to the SSGI (Indonesian Nutritional Status Survey). The national stunting prevalence is 19.8%. While the target for 2025 is 18.8%, the Indonesian government must continue to strive to reduce stunting cases to reach the target of 18.8%. The government program to provide free nutritious food for pregnant and breastfeeding mothers and children aged 2-5 years has been implemented as an effort to reduce stunting cases, but the issue of maternal height also affects the incidence of stunting. Women of childbearing age who are under 150 cm tall are at high risk of giving birth to stunted babies. Yogyakarta is one of the developed cities in Indonesia known as a city of education, but still has quite high cases of stunting in toddlers in one of the districts in Gunung Kidul. Although maternal height has been identified as a risk factor for stunting, local evidence shows that areas with a higher burden of stunting incidence, such as in the Rongkop Community Health Center working area, have stunting incidences of 60 respondents out of a total of 148 toddlers in 2025. The purpose of this study was to determine the relationship between maternal height and the incidence of stunting in toddlers at the Rongkop Community Health Center, Gunung Kidul in 2025. This study used a quantitative method with a cross-sectional study design, with a total sampling of 148 respondents. Data were analyzed using the chi-square test. The results of the study is that there are 148 respondents who are pregnant with reproductive age characteristics of 20-35 years 85,1%, with employment as a housewife 62,2% and the highest level of education is senior high school 45,9%. Mother's height data short <150 cm is 14,2% and all of them gave birth to incidence of stunting toddlers. The results of the Chi-Square analysis showed a significant relationship (0.001 <0.05). Conclusion There is a relationship between maternal height and the incidence of stunting in toddlers at Rongkop Community Health Center, Gunung Kidul Regency in 2025.